Workshop Edukatif Manasik Haji Anak Berbasis Experiential Learning: Upaya Membangun Pemahaman Dini tentang Rukun dan Makna Haji di SD Al Azhar 7 Sukabumi : Penelitian - Latif (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This educational hajj workshop for children aims to instill an early understanding of the pillars and meaning of the hajj pilgrimage among students at SD Al Azhar 7 Sukabumi through the experiential learning approach. This method was chosen because it involves direct experiences, reflection, and active student participation in the learning process. The workshop activities included hajj simulations, educational games, interactive discussions, and reflective assignments. The results showed an improvement in students' cognitive understanding of the hajj rituals, as well as the development of spiritual awareness about its values. The experiential learning approach proved effective in helping children grasp abstract religious concepts in a concrete and meaningful way. This workshop also contributed to instilling Islamic character values such as patience, discipline, and togetherness from an early age. It is recommended as an engaging and applicable model of religious education for elementary schools.